(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Ovarian cancer is an alarming health problem in Bangladesh. The annual mortality rate per 100,000 people from ovarian cancer in Bangladesh has increased by 40.3% since 1990, an average of 1.8% a year. Globcan predicts a change in the reported incidence of ovarian cancer from 2912 in year 2012 to 3132 in 2015. Recurrent high-grade ovarian cancer is usually associated with short term survival. There are few guidelines to surgically and medically treat long term survivors with ovarian cancer. We are reporting three cases on advance ovarian cancer patients; all are married, age ranging from 40-60 years, primarily treated with chemotherapy. After that, they were experienced with FDA approved (Nov 14, 2014) monoclonal antibody Bevacizumab (AVASTIN), additionally with chemotherapy. Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 157-161